Journey and Immersion. About a Poetics of Sensory in Contemporary Theatre - MUREȘAN, Răzvan (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
In the contemporary theatrical practice we find very frequently different formulas where the role of the audience is explored and its relation with the performer is renegotiated. This paper investigates some of the practices that aim to abolish the traditional boundary between the stage and the audience, counting on its affective participation, on the interaction with the performer or the acting space. In many situations the productions are labeled as immersive, although the term remains ambiguous and generic, the diversity of the spectacular formulas not allowing the establishment of a consensus. Such productions seek a higher degree of the participation of the audience, so that it becomes an active part of the performance, more than a spectator, having the freedom to move in space, to explore freely or guided, to make choices, even to influence in a certain degree the course of the story. The inner world of the characters materializes rather in corporeal expressiveness, in objects, scenographic or sound elements, so that the textual poetry, with its content of meanings and verbal images, is transposed into a sensorial poetics, being favored the gestural, vocal, kinesthetic dimensions. Often the dramatic construction is episodic, fragmented and generates networks of meanings, which are detached from the narrative and the logic of the original textual support, in order to be later individually assembled by each participant.